PROSTITUSI DALAM PERSPEKTIF HAK ASASI MANUSIA DAN ISLAM (STUDI KASUS PRAKTEK PROSTITUSI DI KOTA BENGKULU) - John Kenedi (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2017)
Abstract: Prostitution is a community disease that is difficult to eradicate due to many factors that affect its existence. The various types of prostitution that emerged show how prostitution has grown in society. The condition is further complicated when prostitution seeks to seek protection under human rights. Prostitution seeks the path of protection under human rights through two essentials: Protection of human rights to the work of sex workers and protection of minority status opposed by the wider community. On the other hand, there is a distinction between liberal Westernmade human rights and human rights according to Islam in accordance with the sunatullah, so that the distinction raises different perceptions regarding the issue of prostitution. This paper will reveal whether prostitution is a profession that should be protected as a right to work in human rights, as well as finding the right way out to avoid conflict of interest in human rights so that peace and tranquility can be realizedin society.